2020
DOI: 10.1038/s41467-020-18702-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated molecular characterization reveals potential therapeutic strategies for pulmonary sarcomatoid carcinoma

Abstract: Pulmonary sarcomatoid carcinoma (PSC) is a rare subtype of lung cancer with poor prognosis. Here, we perform multi-omics analysis of 56 PSC samples, 14 of which are microdissected to analyze intratumoral heterogeneity. We report the mutational landscape of PSC. The epithelial and sarcomatoid components share numerous genomic alterations, indicating a common progenitor. We find that epithelial-mesenchymal transition (EMT) plays important roles in the carcinogenesis of PSC. The pan-cancer analysis reveals high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 66 publications
3
49
2
Order By: Relevance
“…17 Meanwhile, NSCLC treatment strategies have shifted from tumor type-centered to histomolecular subtype-directed pattern, which is tailored to a specific cluster of patients and can provide better efficacy than traditional treatments. [18][19][20] In the realm of PSC, although several previous studies have highlighted its genomic structures using NGS, 14,21 no widely accepted subtyping strategy of PSC has been introduced so far, hampering the precise treatment of PSC. And considering the high costs of genomic profiling and the convenience of immunohistochemistry (IHC), pathology staining derived subtyping strategies might be an economical alternative for the genetic subtyping method.…”
Section: Introductionmentioning
confidence: 99%
“…17 Meanwhile, NSCLC treatment strategies have shifted from tumor type-centered to histomolecular subtype-directed pattern, which is tailored to a specific cluster of patients and can provide better efficacy than traditional treatments. [18][19][20] In the realm of PSC, although several previous studies have highlighted its genomic structures using NGS, 14,21 no widely accepted subtyping strategy of PSC has been introduced so far, hampering the precise treatment of PSC. And considering the high costs of genomic profiling and the convenience of immunohistochemistry (IHC), pathology staining derived subtyping strategies might be an economical alternative for the genetic subtyping method.…”
Section: Introductionmentioning
confidence: 99%
“…TP53 appears to play a particularly important role in PSC. It is the most frequently mutated gene in this condition (74–79%) and most of the reported mutations lead to gene inactivation [ 8 , 11 , 12 ]. TP53 mutations are also found with high frequency (50–52%) in lung ADC [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTEN lies upstream of the phosphoinositide 3-kinase (PI3K)-AKT-mammalian target of the rapamycin (mTOR) axis, which has broad roles in directing cellular growth, metabolism, division, senescence, and migration [ 15 ]. Loss of PTEN expression has been described in approximately 9% in PSC [ 11 ] and occurs in 5–10% of ADC [ 14 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently mutated genes across different studies include TP53, KRAS, CDKN2A, PTEN, MET, EGFR, BRAF, and HER2 [12][13][14]. In a cohort of PSC cases, 79% (44/56) of the patients harbored mutations in TP53, and 57% of the patients harbored mutations in genes of the receptor tyrosine kinase (RTK)/RAS pathway: EGFR (16%), KRAS (14%), MET (13%), BRAF (7%), NF1 (5%), and NRAS (4%) [14]. Schorock et al revealed a 0.8% (1/12) RET proto-oncogene ampli cation in PSC [12], and Liang et al found two PSC patients (2/32) with RET fusions, KIF5B-RET and TUBD1-RET [13].…”
Section: Introductionmentioning
confidence: 99%